Early Complications Following Minimally Invasive Surgery for Hallux Valgus in Patients with and without Diabetes - Virginia M. Cafruni MD; Matias A. Novillo Hinostroza; Ana C. Parise MD; Leonardo A. Conti MBA, PhD; Nelly M. Carrasco MD; Daniel S. Villena MD; Pablo Sotelano MD; Maria Gala Santini Araujo MD (Foot & Ankle Orthopaedics, 2022)
Category: Diabetes; Bunion; Midfoot/Forefoot Introduction/Purpose: Diabetes mellitus (DM) is a chronic disease with a high worldwide prevalence. People with DM are more likely to develop complications compared to non-diabetic patients undergoing foot and ankle surgery. Currently, orthopedic surgery tends to use minimally invasive surgery (MIS), this resource is used to successfully solve forefoot deformities such as Hallux Valgus (HV). So far there is no evidence enough on this type of surgery and its complications in people with DM. The objective of this study is to determine the types and rates of early complications of elective MIS procedure for hallux valgus in a population of diabetic patients (DBT) compared to a control group of non-diabetic patients (NDBT). Methods: This retrospective study was carried out at our institution between October 2017 and August 2020. During the study period, 874 feet were operated on with MIS technique. All diabetic adults with a diagnosis of HV who underwent percutaneous correction surgery with distal metaphyseal osteotomy and a minimum follow-up of 6 months were included. All diabetic patients who underwent surgery had controlled diabetes with glycosylated hemoglobin less than 7%.For each DBT patient, we randomly selected two aged-matched patients +-1 year without DM as controls. In bilateral surgery, only the first operated foot was taken into account. Patients with previous foot surgery, open lesions or history of previous ulceration, Charcot's neuropathy, metatarsophalangeal osteoarthritis, peripheral vascular disease, and incomplete clinical history were excluded. Complications were recorded and defined as any deviation from the normal postoperative course. Results: A total of 75 patients were analyzed, 25 DBT and 50 NDBT. The follow-up was 10.8 months (6-48). There were no significant differences in demographic characteristics except for the body mass index and the Charlson comorbidity index, both of them were higher in the DBT group (p = <0.001). The complication rate was 18% (n = 9) in NDBT and 24% (n = 6) in DBT patients (p=0.553). There were also no significant differences in the different types of complications. Table 1. It is important to highlight that 7 of 9 complications of the NDBT group required a new surgical intervention (5 osteosynthesis extractions, 1 pseudarthrosis treatment and 1 toilette). In the DBT group, superficial infections were successfully treated with oral antibiotics. Conclusion: This would be the first study that specifically evaluates complications in diabetes patients with elective hallux valgus MIS correction. In our results, diabetic patients have not been associated with a higher rate of complications compared to non- diabetic patients.